TiO2/Cu2O heterojunctions for photovoltaic cells application produced by reactive magnetron sputtering. (2021) - Wisz, G.; Sawicka-Chudy, P.; Yavorskyi, R.; Potera, P.; Bester, M.; Głowa, Ł.
Abstract: In this work, TiO2 /Cu2 O heterostructures were obtained in a two-step process with a direct current magnetron sputtering method. We studied the morphological properties and composition of the thin films by scanning electron microscopy. Optical properties and energy bands at the heterojunction were recorded using a spectrophotometer. Additionally, the current–voltage characteristics examined in both total darkness and with illumination were estimated to have an irradiation (radiation flux divided by area) of 1000 W/m 2 .